An evaluation on information management: A case study of a national public organization - Hassan, Suhaidi; Abu Bakar, Juliana Aida; Omar, Mohd Hasbullah; Mohamed Tahir, Hatim; Abu Seman, Mohamad Amir (2005)
As the business environment nowadays faces stiff competition and as information and communication technology increase in sophistication and complexity, organizations are facing even more challenges and difficulties in managing information. Therefore, it is vital for organizations to evaluate their information management on regular basis in order to gain competitive advantages. This paper presents an overview of an evaluation on information management involving information storage, information processing, and information retrieval in a national public organization. The primary data was collected by means of field visits, series of observation and semi-structured interviews with key personnel of the organization. This paper also discusses on complications encountered when having different systems with different platforms, information security considerations when dealing with ISs and technologies outsourcing projects, and consequences of having very dependent on outside vendors. It further suggests several recommendations to improve the information management of such organization.